Sustainability (disclosure and report format) and firm performance in India. Effects of mandatory CSR reporting - Kofi Mintah Oware; Thomas Adomah Worae (Cogent Business & Management, 2023)
This study aims to determine how sustainability reporting disclosures and report format affect company performance in India's mandatory reporting environment. The study employed feasible generalised least square, panel-correlated standard errors and probit regression. The sample size is 80, and the study period is between 2010 and 2020. We find that utilizing Business Responsibility Reporting (BRR) criteria as sustainability disclosures, have a positive and statistically significant relationship with business value (Tobin's q) and market performance (SPR). Similarly, Global Reporting Initiative (GRI) sustainability reporting disclosures positively influence the SPR and adversely affect Tobin's q. The study shows that BRR sustainability reporting disclosure and mandatory reporting have an interactive and positive influence on Tobin's q. Also, we see that the stand-alone sustainability reporting format positively influences market performance (SPR). Lastly, we see that a firm with a mandatory reporting responsibility will choose a report format (i.e. stand-alone) to disclose its sustainability activities. The implication from the study shows that firms that continue to employ GRI sustainability reporting in India should be aware that it does not send out sound signals that can lead to a rise in firm value or improve long-term performance.
Keywords: 650; firm performance; GRI and BRR sustainability disclosures; mandatory reporting; report format; signalling theory and institutional theory